KEBIJKAN PENGUATAN PENDIDIKAN ISLAM PADA ANAK USIA DINI: STUDI ANALISIS IMPLEMENTASI DAN MODEL INTEGRATIF - Muhammad, Devy Habibi; Tobroni, Tobroni (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
The purpose of this study is to determine the policy of strengthening Islamic education for early childhood. The policy of Islamic Religious Education in PAUD is present as an answer to the need for inclusive and equitable Islamic religious education in Indonesia. The method used in this study is to adopt a qualitative approach with a literature study method. The results of the study show that the Implementation of PAI in Early Childhood Education (PAUD) and Kindergarten (TK) is based on various regulations and laws, such as the 1945 Constitution, Law Number 20 of 2003 concerning the National Education System, as well as the Regulation of the Minister of Education and Culture and the Regulation of the Minister of Religion. The management of PAI in TK and PAUD follows holistic and integrative principles, with two main models, namely Integrated PAI and Special PAI. This model ensures that PAI learning can be adjusted to the needs and development of children, and is integrated with physical-motor, cognitive, language, social-emotional, and art aspects. The management of PAI in Kindergarten and PAUD follows holistic and integrative principles, with two main models, namely Integrated PAI and Special PAI.